Prohibition vs Persistence: Contract Marriages between the Objectives of Islamic Law and Local Legal Realities in Indonesia - Burhan Latip; Muhammad Husni Abdulah Pakarti; Nik Salida Suhaila Nik Saleh; Muhammad Zakir Husain; Normadiah Daud (An-Nisa: Journal of Islamic Family Law, 2025)
The phenomenon of contract marriage (nikah kontrak) in Cianjur Regency has emerged as a significant legal and socio-religious issue within Indonesian society, attracting both national and international scholarly attention. This study is driven by two core research questions: (1) How is Regent Regulation No. 38 of 2021 implemented in addressing the practice of contract marriage? and (2) To what extent does this regulation reflect and uphold the objectives of Islamic law (Maqāṣid al-Sharīʿah)? The research aims to critically examine the legal implementation and social impact of the regulation, particularly on individuals involved in contract marriages. Employing a qualitative method with a descriptive-analytical and case-study approach, data were collected through in-depth interviews with contract marriage actors, community leaders, and government officials. The findings reveal that contract marriages in Cianjur occur through various forms of informal or semi-formal arrangements often without legal guardians or witnesses, or with invalid ones thereby fulfilling only the outward form of marriage without generating legal consequences such as the obligation of ʿiddah. From the Sunni legal perspective, such practices are considered invalid, whereas in the Shiʿa Imamiyah tradition, they may resemble nikah mutʿah under specific conditions. The persistence of contract marriage is influenced by internal factors (economic necessity, cultural accommodation) and external factors (social tolerance and weak enforcement). Although Regent Regulation No. 38/2021 seeks to curb the practice, its implementation has yet to produce a substantial deterrent effect. Within the broader global discourse on Islamic legal reform, this study underscores the necessity of integrating normative Islamic legal principles with contextual socio-legal realities. A more comprehensive strategy combining legal enforcement, community education, and theological engagement is essential to safeguard the higher objectives of Islamic law and protect vulnerable parties in marital relations.